School Environment and Its Influence on Student Environmental Attitudes at SMA Negeri 13 Maros South Sulawesi - Riskawati, Riskawati; Malik, Abdul; Baharuddin, Ichsan Invanni; Musyawarah, Rahma (GEOGRAPHIA : Jurnal Pendidikan dan Penelitian Geografi, 2025)
Environmental issues are a major concern in today s society and students as future leaders have the potential to drive positive environmental change However observations at SMA Negeri 13 Maros revealed that students attitudes towards environmental concern have not fully developed This research explores how the school environment influences students environmental awareness and ability to engage in environmentally conscious behavior The approach used was quantitative descriptive involving 78 samples with purposive sampling techniques The results showed that the physical environment of the school had a positive and significant effect on the attitude of the students environment with a coefficient of B = 0 238 = 0 330 t = 2 823 and p = 0 006 lt; 0 05 Meanwhile the school s social environment showed that it had a positive but insignificant effect with values of B = 0 179 = 0 204 t = 1 747 and p = 0 085 gt;0 05 This shows that the physical environment of the school has a stronger influence than the social environment These findings imply that schools should prioritize the development and improvement of the physical environment by creating more green space and building sustainable infrastructure to effectively foster students environmentally caring attitudes < em>< p>